Strategi Pengembangan Bisnis Tanaman Porang Oleh PT.Kawanua Konjac Nusantara Di Kawangkoan Utara Kabupaten Minahasa - Sinaga, Greatness Morany; Lolowang, Tommy Ferdy; Talumingan, Celcius (Sam Ratulangi University, 2023)
This study aims to identify internal and external factors and analyze the business development strategy of Porang plant at PT.Kawanua Konjac Nusantara. The research was conducted from March to May 2023. The technique of determining informants in this study was purposive with data collection techniques through interviews, observations, questionnaires and literature studies. The data used are primary data and secondary data. Primary data were collected through interviews, based on questionnaires, to the director and company manager of PT.Kawanua Konjac Nusantara, North Sulawesi Provincial Agriculture Office, North Sulawesi Provincial Industry and Trade Office, Plant Cultivation Research Institute, and Food Processing Engineering Research Institute. Secondary data was obtained through books obtained from local bookstores and the internet through google scholar in the form of books, journal articles and theses related to the topic of this research, namely the Porang Plant Business Development Strategy. The results showed that from the environmental analysis and identification of the company's internal and external factors, as well as the quadrant that shows the company's position is in quadrant I, which supports an aggressive strategy (growth). The strategy that can be used by the company PT.Kawanua Konjac Nusantara is the SO strategy by increasing the supply of raw materials to optimize the performance of processing machines and collaborating and cooperating between competitors to reach the top.